Improving Students Mathematical Critical Thinking Ability and Self Regulated Learning Using Open-Ended Approach - Yanti Yulianti; Utari Sumarmo; Asep Kustiana ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2020)
This study is an experiment with pretest postest control group design having a goal to examine the role of open-ended approach  (OEA) on enchancing student’s mathematical critical thinking ability  (MCTA) and  mathematical self regulated learning  (MSRL). Sample of this study are 59 seventh grade students from two classes selected randomly from 5 classess in in a Junior  High School in Garut. Instruments of this study were an essay  MCTA test, and a MSRL Likert model scale. The study found on MCTA and on MSRL students getting treatment with OEA obtained higher grades than the grades of students taught by SA. The first group students attained MSCA and MSRL at fairly good grade level, while the second group students obtained at medium grade level, and they still encountered some difficulties on solving MCTA tasks. Besides that, the study also found  there is high asociation between MCTA and MSRL  and student performed active learning during OEA lessons.Keywords: mathematical critical thinking ability, self-regulated learning, open-ended approach